Analytical validation and clinical application of urinary vanillylmandelic acid and homovanillic acid by LC–MS/MS for diagnosis of neuroblastoma. (7th February 2019) - Shen, Ying; Li, Huijun; Lu, Jie; Luo, Xia; Guan, Qing; Cheng, Liming
Abstract: Vanillylmandelic acid (VMA) and homovanillic acid (HVA) are clinical biomarkers for diagnosis of neuroblastoma (NB), which commonly occurs in the childhood. Development and application of a robust LC–MS/MS method for fast determination of these biomarkers for optimal laboratory testing of NB is essential in clinical laboratories. In present study, we developed and validated a simple liquid chromatography tandem mass spectrometry (LC–MS/MS) method for quick clinical testing of VMA and HVA for diagnosis of NB. The method was validated according to the current CLSI C62‐A and FDA guidelines. The age‐adjusted pediatric reference intervals and diagnostic performance were evaluated in both 24 h urine and random urine. Injection‐to‐injection time was 3.5 min. Inter‐ and intra‐assay coefficients of variation (CVs) were ≤3.88%. The lower limit of quantification and the limit of detection were 0.50 and 0.25 μmol/L for both VMA and HVA. Recoveries of VMA and HVA were in the ranges of 85–109% and 86–100% with CVs ≤5.76%. This method was free from significant matrix effect, carryover and interference. The establishment of age‐adjusted pediatric reference intervals by this LC–MS/MS method was favorable for the improvement in diagnostic performance, which was crucial for correct interpretation of test results from children in both 24 h and random urine.